PEDAGOGICAL SKILLS OF A TEACHER IN MUSICAL CULTURE LESSONS - Khadichakhan SHARAFUTDINOVA; Najibullo ERGASHEV (Scholar Express Journal, 2023)
This article is devoted to the pedagogical skills of a teacher in musical culture lessons, contains information about the requirements for a musical culture lesson, and the need to pay attention to this area. Also, based on the views of thinkers, the influence of music on the development of the spiritual, moral, psychological and physiological, especially emotional sphere of students is explained. The importance of pedagogical skill, lesson organization and musical abilities of a music culture teacher are highlighted
Keywords: Music; musical culture; lesson